EVALUASI RETENSI HARA PADA LAHAN PADI DI KABUPATEN PAMEKASAN - Khofifah Nur Syamsiyah; Kurniawan Sigit Wicaksono (Jurnal Tanah dan Sumberdaya Lahan, 2023)
Rice production in Pamekasan Regency from 2011 to 2019 decreased by 38.71% due to farmers applying fertilizers that did not match plant needs, such as insufficient application of manure, organic fertilizers and other inorganic fertilizers. In addition, the basic fertilization obtained by farmers comes from informal information, so the application of fertilizers on the land is not efficient. Efforts have been made to overcome these problems by evaluating soil fertility from the aspect of nutrient retention as a basis for determining fertilizer requirements. The purpose of this study was to evaluate soil fertility, especially from the aspect of nutrient retention in paddy fields in Pamekasan Regency. This research used a purposive random sampling method based on SPL (Land Map Unit). Parameters observed were cation exchange capacity, organic C, base saturation, pH, electrical conductivity, texture, porosity, bulk density and saturated hydraulic conductivity. The results showed that the high level of soil fertility in Pamekasan Regency was found in cation exchange capacity in Tlanakan District (43.92 cmol kg-1), base saturation in Galis District (99.38%), pH in Tlanakan District (7.00), electrical conductivity in Pakong and Pasean districts (0.39 mS) and the dominant texture is the clay fraction. Low fertility levels are found in soil organic C in Waru and Kadur Districts (0.08%), bulk density in Pasean District (1.59 g cm-3), porosity in Proppo District (34.89%), and saturated hydraulic conductivity in Pasean District (46.34 cm hour-1).